Gagasan Penataan Mekanisme Impeachment Presiden dan/atau Wakil Presiden dalam Ketatanegaraan Indonesia - Rahmah Nur Hasanah; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In a country, the role of a head of state in this case called the Executive is very important. That thereis power given to him. Executive power is the power that holds the highest administrative authority of thestate. The President's power seems very broad and is not explained in detail in the constitution. However, itdoes not mean unlimited presidential power. To compensate for the President's power, supervision is neededwhich leads to the process of Impeachment. One of the dynamics of constitutionality that clearly shows theclose relationship between legal processes and political processes is the process of dismissing the Presidentand / or Vice President as head of state. The process of dismissal of the President / or Vice-President isknown in the practice of constitution in various countries, in terms of this constitutional process referred toas Impeachment. The 1945 Constitution has undergone 4 (four) changes, one of the changes determinedthrough the fourth amendment to the 1945 Constitution is the direct election of the President and hisdismissal through a judicial process that is in addition to the DPR and MPR also involving theConstitutional Court in it.The research used is normative legal research, normative legal research is library legal researchconducted by examining library materials or secondary data. This study uses a research methodology forlegal principles. This research starts from certain fields of legal (written) governance, by first identifying thelegal rules that have been formulated in certain laws.From the results of the research that the authors did, it can be concluded that first, the process ofImpeachment of the President and / or Deputy President in Indonesia was initially regulated before theamendment to the 1945 Constitution. proposal by the DPR. Third, the MPR was made as a breakerinstitution due to the mandate of the 1945 Constitution and Representatives of the people in terms ofdeciding the Impeachment case against the President and / or Vice President in Indonesia.Keywords: Impeachment - President and / or Vice President – Constitution - Mechanism